Między codziennością a „państwem Platona”. Racjonalistyczne aspekty twórczości Łukasza Opalińskiego - Raubo, Grzegorz (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article specifies the role of rationalism in the work of a distinguished Baroque author, Łukasz Opaliński. The source material for the study consists of: Rozmowa Plebana z Ziemianinem (1641), Polonia defensa contra Ioan[nem] Barclaium (1648), Coś nowego (1652), Pauli Naeoceli de officiis libri tres (1659), Poeta nowy (1661–1662). Łukasz Opaliński stated that reason is the most important cognitive faculty of the human being. Reason makes it possible to understand the rules of natural law, which is the source of ethical action among humans, and brings on understanding of the eschatological aim of human life, that is salvation. The possibilities of rational explanation do not, however, encompass the mysteries of religious faith or the basic concepts of natural philosophy, such as the elements, which are the principal components of matter. Rationalism belongs to the principal ideas of Opaliński’s political philosophy. He opted for a rational organization of the state and for rational ways of solving social problems (he underscored the role of common sense, rational dialogue of citizens and rational responsibility for the common good). The political formation that is best suited for rationalization of social life is monarchy. Seeing it as a model government, the author realised that it could not be introduced in the Poland of the 17th century, and consequently, apart from the eulogy of the monarchy, he proposed improvements in gentry democracy, especially in limiting of the “golden freedom”. An important sphere of externalization of Opaliński’s rationalist ideals was his theoretical thought on literature. He critically evaluated some examples of Baroque art of conceit. He underscored the role of rational sources of creativity and rational discipline in structuring a literary work, and his postulates in this field were close to the concepts of classicist criticism.